2012
DOI: 10.1088/0004-637x/757/2/122
|View full text |Cite
|
Sign up to set email alerts
|

The Suppression of Star Formation and the Effect of the Galaxy Environment in Low-Redshift Galaxy Groups

Abstract: Understanding the interaction between galaxies and their surroundings is central to building a coherent picture of galaxy evolution. Here we use Galaxy Evolution Explorer imaging of a statistically representative sample of 23 galaxy groups at z ≈ 0.06 to explore how local and global group environments affect the UV properties and dust-corrected star formation rates (SFRs) of their member galaxies. The data provide SFRs out to beyond 2R 200 in all groups, down to a completeness limit and limiting galaxy stellar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
83
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 62 publications
(121 reference statements)
21
83
1
1
Order By: Relevance
“…A clear trend is observed inward of two to three cluster virial radii: the fraction of gas-rich galaxies decreases monotonically with decreasing cluster-centric distance. This trend is in good agreement with observations that the HI gas depletion increases with decreasing cluster-centric distance inward of about two virial radii (15,18,20,24,(48)(49)(50)(51)(52). Intriguingly, observations indicate that the distribution of star formation rates of cluster galaxies begins to change, compared with the field population, at a cluster-centric radius of about three virial radii.…”
Section: Resultssupporting
confidence: 91%
“…A clear trend is observed inward of two to three cluster virial radii: the fraction of gas-rich galaxies decreases monotonically with decreasing cluster-centric distance. This trend is in good agreement with observations that the HI gas depletion increases with decreasing cluster-centric distance inward of about two virial radii (15,18,20,24,(48)(49)(50)(51)(52). Intriguingly, observations indicate that the distribution of star formation rates of cluster galaxies begins to change, compared with the field population, at a cluster-centric radius of about three virial radii.…”
Section: Resultssupporting
confidence: 91%
“…The correlation within the star-forming galaxies in the low-mass subsample is consistent with the results of some studies, such as Rasmussen et al (2012) who find that starforming galaxies in groups have their star formation suppressed on average by 40% relative to the field and that the trends are more prominent in lower stellar mass galaxies. A direct comparison between the current work and these previous results is difficult given that the environment density metrics differ between the two samples, as does the definition of a star-forming system.…”
Section: Integrated Star Formation Ratessupporting
confidence: 90%
“…At fixed galaxy density and stellar mass, this suppression is stronger in more massive groups. Rasmussen et al (2012a) concluded that the average time scale for quenching the star-formation activity is 2 Gyr and identified a combination of tidal encounters and starvation as the responsible process. 2006) have shown that, for a given velocity dispersion-thus total mass-galaxies in the periphery of clusters have stronger Balmer absorption lines, indicative of younger ages than those located in the cluster core (see Fig.…”
Section: Star Formationmentioning
confidence: 99%